EMAIL AND MAILING LIST - Desy Diana Diana (Majalah SIKOMTEK, 2006)
This day many are starting to use email as a means of correspondence, which quickly andaccurately so there are no limitations of space and time between the sender and the recipientwhile they are still biased to connect to the internet, it will cost you only pay for any freeinternet use. With a variety of benefits that email becomes the means who loved today.